Independent investigation and inquiry body as a solution for the protection of citizens’ human rights - Prastopo Prastopo; Agustinus Purnomo Hadi; Jelli Rita; Ahmad Jaeni; Sugianor Sugianor (Lentera Negeri, 2026)
The protection of human rights in criminal procedure requires not only formal legal guarantees but also an institutional design capable of ensuring independent and impartial investigations. In Indonesia, the concentration of investigative authority within the Indonesian National Police (POLRI) raises concerns regarding the effectiveness of such independence. This study aims to examine whether the current institutional framework under Law No. 20 of 2025 on the Criminal Procedure Code is capable of guaranteeing objective and accountable investigative processes. This research employs a doctrinal legal approach, using statutory and conceptual analyses based on legal materials collected through systematic library research. The analysis applies textual, systematic, and teleological interpretation, supported by deductive reasoning to evaluate the institutional design of investigative authority. The findings indicate that limitations of investigative independence stem from structural factors, including concentration of authority, budgetary dependence, hierarchical organizational culture, and weak oversight mechanisms. These conditions constrain objective law enforcement and weaken human rights protection. This study proposes an Integrated Oversight Framework that combines internal reform, judicial control, and public accountability as a layered model of oversight. However, the framework remains normative and requires further empirical validation and institutional feasibility analysis.